Microarray-based identification of differentially expressed genes associated with andrographolide derivatives-induced resistance in colon and prostate cancer cell lines - Shun, Ying Quah; Charng, Choon Wong; Hui, Chyn Wong; Ho, Kok Lian; Abdul Manan, Nizar; Deb, Pran Kishore; Sagineedu, Sreenivasa Rao; Stanslas, Johnson (Elsevier, 2021)
Chemoresistance poses a major hurdle to cancer treatments. Andrographolide-derived SRJ09 and SRJ23 were reported to exhibit potent, selective inhibitory activities against colon and prostate cancer cells, respectively. In this study, previously developed resistant colon (HCT-116rst09) and prostate (PC-3rst23) cancer cell lines were used to elucidate the molecular mechanisms contributing to chemoresistance. Cytotoxic effects of SRJ09 and SRJ23 on both parental and resistant cells were investigated. Cell cycle distributions in HCT-116rst09 cells following SRJ09 treatment were analysed using flow cytometry. Whole-genome microarray analysis was performed on both parental and resistant cells to obtain differential gene expression profiles. Microarray data were subjected to protein-protein interaction network, functional enrichment, and pathway analyses. Reverse transcription-polymerase chain reaction (RT-PCR) was used to validate the changes in expression levels of selected genes. Besides morphological changes, HCT-116rst09 cells showed 7.0-fold resistance to SRJ09 while PC-3rst23 cells displayed a 5.5-fold resistance to SRJ23, as compared with their respective parental cells. G0/G1-phase cell cycle arrest was observed in HCT-116rst09 cells upon SRJ09 treatment. Collectively, 77 and 21 genes were found differentially modulated in HCT-116rst09 and PC-3rst23 cells, respectively. Subsequent bioinformatics analysis revealed several genes associated with FGFR4 and PI3K pathways, and cancer stemness, were chemoresistance mediators in HCT-116rst09 cells. RT-PCR confirmed the HMOX1 upregulation and ATG12 downregulation protected the PC-3rst23 cells from SRJ23 cytotoxicity. In conclusion, acquired chemoresistance to SRJ09 and SRJ23 in colon and prostate cancer cells, respectively, could be attributed to the alterations in the expression of genes such as those related to PI3K and autophagy pathways.